ENGLISH FOR MARKETING AND PROMOTION : PROGRAM LANGUAGE SHORT COURSE SEBAGAI UPAYA PENINGKATAN MUTU PELAKU UMKM BINAAN RUMAH BUMN KOTA TEGAL - Indrayanti, Iin; Romadhon, Syaefani Arif; Faradis , Nadia Safina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Currently, small businesses in Tegal and the surrounding areas are not proficient in English. Frequently, difficulties in communication hinder the sale of products in foreign markets.The new idea's growth and improvement is being hindered by numerous challenges. The aim of this community service initiative is to support individuals in developing their language skills, particularly in the widely-used English language. Twenty small businesses (MSME) known as UMKM from Brebes, Tegal City/Regency, and Pemalang participated in the event, showcasing products with product export potential (culinary, craft and fashion). The English language training consists of four stages: acquiring new vocabulary, applying the vocabulary, engaging in verbal communication, and composing product descriptions. The participants benefited from the training session by enhancing their vocabulary (100 percent), oral communication abilities (233 percent), and confidence in public speaking without relying on a script. Furthermore, it showed them how to compose product descriptions in English for social media marketing.